Prevalence of Anxiety and Depression among Caregivers of Cancer Patients A Case Study in a Public Hospital in Malaysia - Ahmad, Roslee; Mohd Isa, Azizan; A Rashid, Mohd Radzniwan; Yusoff, Nasir; Mohd Tahir, Lokman; Huda, Miftachul; Marsinun, Rahmiwati (IIUM Medical Journal Malaysia, 2023)
INTRODUCTION: Anxiety and depression are common mental illnesses among cancer caregivers. Most caregivers often sacrifice a lot of time, energy and their own physical and emotional needs. MATERIALS AND METHOD: A cross sectional study was conducted among 156 caregivers of cancer patients who were providing treatment and moral support to cancer patients at the Oncology clinic of Sultan Ismail Hospital (SIH), Johor Bahru, Malaysia. The Hospital Anxiety Depression Scale (HADS) was used to assess the depression and anxiety levels among the respondents. Data was analysed using Statistical Package for Social Sciences version 17.0 software. The P value of less than 0.5 was taken a significant. RESULTS: In general, there was moderate relationship between cancer caregivers and patients in term of emotional, care and patient treatment, but in some circumstances, caregivers were also exposed to risk during care period of cancer patients. There was a significant relationship with moderate correlation between factors of taking care of emotion of patients (p<0.05, r=0.403), their diseases (p<0.05, r=0.456) and treatment (p<0.05, r=0.600) with the level of anxiety. There was a strong correlation between caring and anxiety in the item of lack of attention on patient demand (p< 0.05, r=0.91) and not angry to patient (p<0.83). CONCLUSION: The awareness regarding the anxiety and depression among caregivers need to be increased among health professionals such as physicians and nurses. Although the interventions are aimed to help the patients, but this can also cause anxiety and depression to caregivers.